2011
DOI: 10.1080/08873267.2011.592434
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on marriage and family therapy emergent from international dialogues in China.

Abstract: University of the RockiesFamily is a central construct in Chinese life. Although central, it is also a changing construct as China becomes an increasingly international nation. This article discusses the Chinese family system in context, the challenges to existing constructs, and issues of cultural competence in the midst of change. Using diverse constructs such as pastoral care, existential ethics, and systemic approaches, it is possible to develop means of approaching family life in China both therapeuticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Couples learn to identify with cultural values and biases of their own families throughout their childhood. Family counselors and therapists as well as all their counterparts need to develop activities and intervention techniques to counteract these biases (Dias et al, 2011).…”
Section: Cultural Issues In Family Livingmentioning
confidence: 99%
“…Couples learn to identify with cultural values and biases of their own families throughout their childhood. Family counselors and therapists as well as all their counterparts need to develop activities and intervention techniques to counteract these biases (Dias et al, 2011).…”
Section: Cultural Issues In Family Livingmentioning
confidence: 99%
“…There is an apparent increase in Western family and marital therapy researchers who are interested in the development of marital and family therapy in China despite the language barrier (e.g., Adams et al., ; Dias, Chan, Ungvarsky, Oraker, & Cleare‐Hoffman, ; Liu et al., ; Miller & Fang, ). The Journal of Family Psychotherapy recently devoted a special issue to marriage and family therapy in China (Miller, ).…”
Section: Intriguing Developments In Family Therapy In the People's Rementioning
confidence: 99%
“…Sze, Hou, Lan, and Fang () found that the proportions of the three therapy modalities (individual, couple, and family) differed significantly from western findings in that families predominated, followed by individuals, and then couples in a Beijing psychotherapy center, in comparison to the descending order of individuals, couples, and families in the west. This is intriguing in that, while China is experiencing an increasing rate of divorces (Dias et al., ; Lim et al., ; Miller & Fang, ), fewer people seek couple therapy to improve their marital well‐being. These characteristics seem to suggest that Chinese cultural values prioritize parent–child relationships over the couple relationship.…”
Section: Intriguing Developments In Family Therapy In the People's Rementioning
confidence: 99%
See 1 more Smart Citation
“…It would follow that the same type of process of “broken-ness” occurs in China, yet because family identity is more profound, turning away from one’s family to establish a separate identity may be considered a great humanistic crime. As Dias, Chan, Ungvarsky, Oraker, and Cleare-Hoffman (2011) suggest, “For a Chinese person, to exist is to live your life with your family, which is sufficient for a meaningful life” (p. 271). However, from a contextual standpoint, according to some researchers, when a child has a disability, it may possibly be seen, in some families, as “a punishment for an ancestor’s misbehavior” or that “the disability is due to the current family’s disregard for their obligation to honor their ancestors” (Wang, Michaels, & Day, 2011, p. 784).…”
Section: Disability and Family Identitymentioning
confidence: 99%